Ten new species of the genus Phortica from the Afrotropical and Oriental regions (Diptera: Drosophilidae) - Chen, Hongwei; Máca, Jan (Zootaxa, 2012)
Ten new species of the genus Phortica are described from the Afrotropical and Oriental regions: P. (Allophortica)chingolaensis Chen & Máca, sp. nov., P. (Ashima) eseta Chen, sp. nov., P. (Ashima) mediarista Chen, sp. nov., P. (Ashima)nakanoi Chen, sp. nov., P. (Ashima) biclavata Chen, sp. nov., P. (Phortica) ancistria Chen, sp. nov., P. (Phortica)monoceaena Chen, sp. nov., P. (Phortica) dirhopala Chen, sp. nov., P. (Phortica) ryukyuensis Chen, sp. nov. and P. (Phortica) sumatraensis Chen, sp. nov. A species list of the genus Phortica is provided.